Persistence and Fadeout of Preschool Participation Effects on Early Reading Skills in Low- and Middle-Income Countries - Amber Gove; Eileen Dombrowski; Simon J. King; Jennifer Pressley; Tara Weatherholt (Global Education Review, 2018)
The adoption of the Sustainable Development Goals (SDGs) in September 2015 marked a new milestone for early childhood education, care, and development. For the first time in the framework of global goals, preschool education was described as integral to children’s school readiness. Yet with few exceptions, much of the research on the impact of preschool has stemmed from high-income countries. Even fewer studies have examined preschool participation and later learning across multiple countries. This article helps fill this gap by connecting preschool participation to early primary reading outcomes, as measured by the Early Grade Reading Assessment. Drawing on a unique data set using student-level learning assessments from 16 countries, we use preprimary participation to explain primary school reading skills, including letter knowledge and oral reading fluency. We also model the influence of key demographic variables on these outcomes, including home language and classroom language of instruction (LOI). For a subset of six countries with exceptionally rich data, we examine national-level policy and practice to better understand what might explain the persistence or fadeout of the effect of preschool. Policy makers and practitioners alike will find these results useful in making cases for improving preschool experiences for children in low- and middle-income countries in the next decade of SDG-related efforts.